Mirrors - Chua, Feng Jing (2018)
A short 2D animated film about a man, who wants to be someone else, interacts with a magic mirror. Storyline sparked off in my late night of ideation, when I was in a daze, and gazed at my own reflection in the full length mirror facing my work desk. The theme of the film is, “Stay true to yourself, for you surely belong somewhere”. Pre-production development has been further inspired by my backpack travels to tropical countries and overseas surf trips.